Winter slip-and-fall accidents in Finland: characteristics and views on their prevention - Johannes Mesimäki; Fanny Malin; Merja Penttinen (Traffic Safety Research)
Outdoor falls, such as winter slip-and-fall accidents, represent a substantial pedestrian safety issue in countries with cold and snowy winters like Finland. Such falls are typically not considered traffic accidents nor are they included in traffic safety policy objectives or accident statistics. This survey study aimed to explore experiences of winter slip-and-fall accidents in Finland, estimate their frequency and investigate views regarding their prevention to inform efforts aiming to increase the role of walking. Data was collected with an online survey directed to Finnish residents (n=1,215), which queried the characteristics of slip-and-falls occurring during the winter of 2020–2021, their consequences, and views regarding their prevention. The results suggest that slip-and-falls occur often in Finland, with just over one third of respondents having experienced at least one. Slip-and-falls frequently occurred on yards or pavements and in icy or snowy conditions, and frequently reported contributing factors include unexpected slippery spots on the walking surface, poor winter maintenance and poor footwear traction. Respondents considered improved winter maintenance and using appropriate footwear, such as anti-slip devices, as important ways to prevent falls. The results suggest that the walking during winter in Finland is not safe, and a combination of personal and public measures could result in the most effective strategy to prevent slip-and-falls. The omission of slip-and-fall accidents from traffic safety policy arguably results in a misleading image of pedestrian safety. The results of this study support the inclusion of pedestrian falls as pedestrian single accidents.